A systematic review with meta‐analysis: Efficacy and safety of potassium‐competitive acid blocker compared with proton pump inhibitor in the maintenance of healed erosive esophagitis - Daniel M Simadibrata; Elvira Lesmana; Muhammad I A Pratama; Adrianus J Sugiharta; Afiah S Winarizal; Yeong Y Lee; Ari F Syam (JGH Open, 2024)
Abstract Introduction Proton pump inhibitor (PPI) is the mainstay therapy for the maintenance of healed erosive esophagitis (EE). It is unknown whether potassium‐competitive acid blockers (PCABs) are more efficacious and safer than PPIs. Methods Only randomized controlled trials (RCTs) comparing PCABs to PPIs in the maintenance of healing rates of endoscopically proven healed EE and indexed in MEDLINE, EMBASE, and CENTRAL until 3 February 2024, were included. A fixed‐effects model meta‐analysis was performed to pool primary efficacy outcome (maintenance of healing rates at week 24) and safety data (any treatment‐emergent adverse event or TEAE). The risk of bias was assessed using Cochrane's Risk of Bias 2 (RoB2) tool. Results Four RCTs with a total of 2554 patients were eligible for inclusion. All trials were of low risk of bias. Compared to lansoprazole 15 mg, the maintenance rates of healed EE at week 24 were significantly higher with vonoprazan 10 mg (RR 1.13; 95% CI 1.07–1.19) and vonoprazan 20 mg (RR 1.15; 95% CI 1.10–1.21). Likewise, compared to lansoprazole 15 mg, any TEAEs were significantly greater with vonoprazan 20 mg (RR 1.10; 95% CI 1.01–1.20) but not vonoprazan 10 mg. Conclusion Vonoprazan 10 and 20 mg were superior to lansoprazole 15 mg in the maintenance of the healing of EE. Any TEAEs were greater with vonoprazan 20 mg.